From Margins to Mainstream: The Journey of Scheduled Caste Women through Panchayati Raj Institutions in Haryana, India - H.S. Mangat; Shaik Iftikhar Ahmed; L.S. Gill (Caste)
Taking into account widespread illiteracy among elected Panchayati Raj Institutions (PRIs) in 2010, as 30.06 PRIs were illiterate against the 24.45 per cent general rate of illiteracy in the state, the government of Haryana enacted Panchayati Raj Amendment Act, 2015; under which educational qualifications have been made mandatory to participate in the PRIs elections. This amendment has been based on the premise that educated PRIs will be playing a more constructive role for development at village, block and district levels. Since Scheduled Caste (SC) women are less educated, therefore this study is addressed to assess the impact of the amended Act on the empowerment of SC women. The study reveals that the share of SC women PRIs among the total PRIs increased from 11.32 per cent in 2010 to 13.41 per cent in 2016, while the composite score attained by them increased from 45.65 in 2010 to 129.29 in 2016.